LOCALIZATION TRAJECTORY AND CRITICAL INDEX - Zharekeshev, Isa Kh. (Хабаршы. Физика сериясы, 2018)
Electron localization in chaotic systems is studied by using the method of transfer-matrices. The critical index of the localization length is found.